Measurement and prediction of antimicrobial resistance in bloodstream infections by ESKAPE pathogens and Escherichia coli. (December 2019) - De Socio, Giuseppe Vittorio; Rubbioni, Paola; Botta, Daniele; Cenci, Elio; Belati, Alessandra; Paggi, Riccardo; Pasticci, Maria Bruna; Mencacci, Antonella
Highlights: A cumulative antimicrobial resistance index (ARI) for ESKAPE pathogens and Escherichia coli (ESKAPEEc) is proposed. ARI is a key outcome measure of antimicrobial stewardship programmes and tool to predict antimicrobial resistance trends. The cumulative ESKAPEEc mean ARI increased significantly from 0.200 ± 0.01 in 2014 to 0.276 ± 0.02 in 2018. A mathematical prediction model for antimicrobial resistance trends was obtained. In the absence specific antimicrobial stewardship, pandrug resistance could be expected within the next 8–15 years. Abstract: Objectives: This study aimed to evaluate a cumulative antimicrobial resistance index (ARI) as a possible key outcome measure of antimicrobial stewardship programmes (ASPs) and a tool to predict the antimicrobial resistance (AMR) trend. Methods: Antimicrobial susceptibility for Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, Enterobacter spp. and Escherichia coli (ESKAPEEc) pathogens recovered from blood cultures during a 5-year period (2014–2018) was analysed to obtain a cumulative ARI. For each antibiotic tested, a score of 0, 0.5 or 1 was assigned for susceptibility, intermediate resistance or resistance, respectively, and the ARI was calculated by dividing the sum of these scores by the number of antibiotics tested. Cumulative ARIs of ESKAPEEc micro-organisms were compared and a mathematical prediction model for AMR trend was obtained. Results: In total, 1858 ESKAPEEc isolates were included in the study. The cumulative ESKAPEEc mean ARI increased significantly from 0.200 ± 0.01 in 2014 to 0.276 ± 0.02 in 2018 ( P  < 0.001). In multivariable regression analysis, factors significantly associated with ARI ≥ 0.5 were E. faecium, K. pneumoniae, P. aeruginosa and A. baumannii infection ( P  < 0.001) and infection occurring after 2014 ( P  < 0.05). Based on the prediction model obtained, in the absence of any interventional measure, a tendency to pandrug resistance of the ESKAPEEc group could be expected in the next 8–15 years. Conclusion: The ARI could be a useful tool to measure the impact of ASPs on AMR. The increasing incidence of AMR among ESKAPEEc organisms underscores the needing for ASPs.